THE INFLUENCE OF WORK LIFE BALANCE, INTERNAL COMMUNICATION, AND TEAM WORK ON EMPLOYEE PERFORMANCE AT PT. BANK SUMUT CABANG KOORDINATOR MEDAN - Dwi Indah Lestari; Anggia Sari Lubis; Melisa Zuriani Hasibuan; Horia Siregar (Universitas Efarina, 2025)
This research aims to determine the effect of work-life balance, internal communication, and teamwork on employee performance at PT. Bank Sumut Medan Coordinator Branch. The approach used is a quantitative method, with a population of 125 employees and a sample of 56 respondents determined through simple random sampling using the Slovin formula. Data collection was conducted through observation and interviews, while data analysis used multiple linear regression with the help of SPSS version 26 software. The results show that partially, work-life balance and internal communication have a positive and significant effect on employee performance. Meanwhile, teamwork does not have a significant impact on employee performance. Simultaneously, the three independent variables significantly influence employee performance with a coefficient of determination (R²) of 0.971, which means 97.1% of the variation in employee performance can be explained by work-life balance, internal communication, and teamwork. This finding indicates the importance of managing work balance and effective communication in supporting the improvement of human resource performance in the banking work environment.